Literature Review: The Effectiveness of Kinesiotaping and Hydrotherapy in Improving The Quality of Life of The Elderly With Osteoarthritis - Abdullah Alba Nur Ihza (Gaster, 2021)
The number of elderly people in Indonesia continues to increase every year. The high rate of increase in the elderly is a concern for all people, because the elderly tend to be vulnerable to various kinds of diseases. Osteoarthritis is the most common disease in the world with a prevalence of 15.5% in men and 12.7% in women in Central Java. Handling that can be given to the elderly with osteoarthritis is by providing kinesio taping and hydrotherapy exercises. Purpose: The purpose of this literature review is to review the effectiveness of giving kinesio taping and hydrotherapy exercises to improve the quality of life of the elderly with osteoarthritis according to evidence based. Methods: This research is a literature study that summarizes several relevant literatures with the same theme. Literature search using 2 databases, namely Pubmed and Google Shcolar. The keywords used in the literature search included: â€œKinesio tapingâ€, â€œhydrotherapyâ€, â€œosteoarthritisâ€ and â€œquality of lifeâ€. Results: Based on the results of a literature review, it was found that the addition of kinesiotaping and hydrotherapy exercises can affect the quality of life of the elderly with osteoarthritis. Conclusion: The conclusion from this literature review shows that the addition of kinesio taping to conventional exercise and the provision of hydrotherapy exercises can both improve the quality of life of the elderly with osteoarthritis which can be measured with a quality of life measuring instrument in the form of WOMAC.Â